Usage of prestressed vertical bolts for retrofitting flat slabs damaged due to punching shear - Hamed S. Askar (Alexandria Engineering Journal, 2015)
Sometimes, due to design mistakes or a change in the construction function results in heavier or additional loads, a flat slab may be failed by punching shear which is considered as a brittle failure. A lot of research work has been carried with the objectives of strengthening existing flat slabs against punching shear. Nevertheless, very few experimental tests have been conducted for the investigation of the behavior of repaired flat slabs damaged due to punching shear. An experimental investigation with the objective of retrofitting flat slabs damaged due to punching shear using prestressed vertical bolts is presented in this paper. The parameters examined in this study are vertical prestressed bolts with different ratios within the slab thickness, slab thickness and central column size. Through the experimental tests the load carrying capacity, deformation characteristics and the cracking behavior have been investigated. A comparison between the behavior of retrofitted slabs and their references showed that the proposed system of repair is effective and could be used in practice. A comparison between the experimental results and calculated punching failure load based on the formulas adopted by different codes, showed a reasonable agreement.